1969
DOI: 10.1136/jcp.22.3.296
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology of extrahepatic epithelial iron deposits in siderosis in Bantu

Abstract: SYNOPSIS Twenty-seven specimens of human tissue, obtained by operation, were tested to evaluate the theory that iron uptake by tissues from serum is greater when transferrin is nearly completely saturated than when the degree of saturation is normal.Samples of each tissue were incubated in autologous serum so prepared that in one instance the transferrin was 50 % saturated and in the second 90 % saturated with iron containing 59Fe.In all samples the uptake of iron was greater from the transferrin which was 90 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1971
1971
2004
2004

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…The results of this investigation confirm those already demonstrated that high percentage saturation of transferrin by iron is in some measure responsible for uptake of this element by thyroid tissue (Buchanan, 1969). While high degrees of transferrin saturation increase uptake in most cases it is clear that some uptake also occurs from transferrin only 50% saturated.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The results of this investigation confirm those already demonstrated that high percentage saturation of transferrin by iron is in some measure responsible for uptake of this element by thyroid tissue (Buchanan, 1969). While high degrees of transferrin saturation increase uptake in most cases it is clear that some uptake also occurs from transferrin only 50% saturated.…”
Section: Discussionsupporting
confidence: 90%
“…Thyroid was used in this investigation because of its ready availability and because it is known to take up 328 iron well (Buchanan, 1969). In all cases partial thyroidectomy had been performed for colloid goitre.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The high levels of iron present in this beverage were caused by the preparation of the beer in iron kettles . Recently, a genetic defect relating to this condition has also been discussed (1)(2)(3)(4)(5)(6).…”
mentioning
confidence: 99%